Training on the Utilization of Climate Smart Moisture and Nutrient Monitoring Tools among Lead Smallholder Horticulture Farmers in Uganda - Barungi, Julian; Okonya, Joshua; Ilakut, Ben; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Decision support tools, especially those that provide relevant data in a quick and user-friendly manner, are critical in helping farmers make better decisions in their operations, including crop production and irrigation water use. To address the challenges of unsustainable irrigation water use, related water use conflicts and high nutrient leaching in the Mubuku Irrigation Scheme in Uganda, the training enhanced capacities of 70 participants (46 males, 24 females) comprising smallholder horticulture farmers, extension workers, irrigation scheme technicians and District Local Government Officials on the utilization of climate-smart moisture and nutrient monitoring tools. The tools are a collection of chameleon field readers, wetting front detectors, chameleon EC meters, and chameleon nitrate strips that work together to help farmers assess soil moisture, saturation, and nitrate levels.